Implementasi Good Money Habit pada Mahasiswa KIP Kuliah Politeknik Negeri Medan - Karina Adelia; Rikwan Efendi Salam Manik (Jurnal Manajemen Riset Inovasi, 2026)
KIP Kuliah is a government-funded educational assistance program aimed at high school (SMA) graduates or equivalent who demonstrate strong academic potential but face economic constraints. This program is expected to expand access to higher education and help students complete their studies on time without being burdened by financial concerns. However, the effectiveness of KIP Kuliah utilization depends not only on the amount of aid provided but also on students’ ability to manage their finances wisely through the implementation of good money habits This study is a field research using a descriptive qualitative approach. The sample consists of six informants, namely KIP Kuliah recipients at Politeknik Negeri Medan from the 2020–2023 cohorts. The results show that personal financial management among students includes budgeting, controlling expenses, and saving behavior. In addition, several factors influence students’ financial behavior, such as financial literacy, social environment, lifestyle, and individual needs. With proper financial management, KIP Kuliah funds can be utilized optimally to support students’ academic success.